Bibliometric Analysis: Problem-Based Learning, Problem-Solving Skills, Self-Regulated Learning Assisted by Geogebra in Vocational High School - Setyani, Arie; Masrukan; Kurniasih, Ary Woro (Indonesian Journal of Mathematics Education, 2025)
This study aims to analyze the bibliometric mapping of vocational high school mathematics research from 2020 to 2024 to address the research gap on problem-solving skills in the problem-based learning model assisted by GeoGebra, with a focus on students’ self-regulated learning in vocational high school. The data collected focuses on the keywords "mathematics, problem-solving, self-regulated learning, GeoGebra" to identify journals published between 2020 and 2024, using Google Scholar as the data source through Publish or Perish to gather data and Harzing's VOSviewer for bibliometric mapping. This study identified seven articles related to the keywords. The research follows the PRISMA systematic review method. The findings indicate that publications on problem-solving skills within the problem-based learning model assisted by GeoGebra, viewed from students' self-regulated learning in vocational high school, still have the potential to grow in the coming years. Moreover, problem-based learning positively impacts students' self-regulated learning and problem-solving skills in vocational high school.